PENGEMBANGAN PROTOTYPE USER INTERFACE DAN USER EXPERIENCE UNYOne: APLIKASI ONE-STOP-SERVICE MENGGUNAKAN METODE USER-CENTERED DESIGN - Was, Menara Lintang; Nurkhamid (Department of Electronics and Informatics Engineering Education, 2024)
In today's digital era, information technology and mobile applications have become an integral part of everyday life, including in the field of education. However, the use of this technology often faces various problems, such as integration with other systems, as well as inadequate User Interface (UI) and User Experience (UX), causing discomfort and confusion for users, especially students. Therefore, this study aims to (1) create UI and UX prototypes that can improve students' experience in accessing academic information through a one-stop-service model, and (2) evaluate the feasibility of these prototypes. This research uses the Research and Development method with a User-Centered Design approach according to ISO 9421-210 standards, including analysis of usage context, user needs analysis, design solution development, and evaluation of design solutions based on effectiveness, efficiency, and user satisfaction. The results of this study include the interface design and User Experience of the UNYOne application as an academic and student service one-stop-service at Universitas Negeri Yogyakarta. Evaluation of UNYOne showed an effectiveness rate of 98%, an efficiency rate of 93.1%, and a user satisfaction rate of 91.1%, with a usability rate of 94.06%, indicating that UNYOne has excellent quality in meeting user needs and satisfaction